Severe COVID‐19 during pregnancy in Sweden, Norway, and Denmark - Anne K. Örtqvist; Maria C. Magnus; Anna J. M. Aabakke; Stine Kjaer Urhoj; Anne Vinkel Hansen; Anne‐Marie Nybo Andersen; Lone Krebs; Karin Pettersson; Siri E. Håberg; Olof Stephansson (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Pregnancy is a risk factor for severe coronavirus disease 2019 (COVID‐19) and adverse pregnancy outcomes. We aimed to explore maternal characteristics, pregnancy outcomes, vaccination status, and virus variants among pregnant women admitted to intensive care units (ICU) with severe COVID‐19. Material and methods We identified pregnant women admitted to ICU in Sweden (n = 96), Norway (n = 31), and Denmark (n = 16) because of severe COVID‐19, from national registers and clinical databases between March 2020 and February 2022 (Denmark), August 2022 (Sweden), or December 2022 (Norway). Their background characteristics, pregnancy outcome, and vaccination status were compared with all birthing women and severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) test‐positive pregnant women during the same time period. We calculated the number admitted to ICU per 10 000 birthing and per 1000 SARS‐CoV‐2 test‐positive women during the Index, Alpha, Delta, and Omicron periods. Results Women admitted to ICU had a higher mean body mass index, were more often of non‐Scandinavian origin, had on average lower education and income levels, had a higher proportion of chronic and pregnancy‐related conditions, delivered preterm, had neonates with low Apgar scores, and had more infants admitted to neonatal care, compared with all birthing and test‐positive pregnant women. Of those admitted to ICU, only 7% had been vaccinated before admission. Overall, the highest proportion of women admitted to ICU per birthing was during the Delta period (4.1 per 10 000 birthing women). In Norway, the highest proportion admitted to ICU per test‐positive pregnant women was during the Delta period (17.8 per 1000 test‐positive), whereas the highest proportion of admitted per test‐positive in Sweden and Denmark was seen during the Index period (15.4 and 8.9 per 1000 test‐positive, respectively). Conclusions Admission to ICU because of COVID‐19 in pregnancy was a rare event in the Scandinavian countries, but women who were unvaccinated, of non‐Scandinavian origin, and with lower socio‐economic status were at higher risk of admission to ICU. In addition, women admitted to ICU for COVID‐19 had higher risk of adverse pregnancy outcomes.